The soul words of the Ukrainian people - Boltivets, Sergii (Psyhology & society, 2022)
The article presents the main directions of the domestic psychological science development which are devoted to the psychology of the Ukrainian person and the Ukrainian people in the context of methodolohems of their self-cognition and self-affirmation. It is noted that the changeability of the meanings of the same word forms reflects the peculiarities of human thinking of each era and therefore, through the existence of the mental, determines the meaningfulness of being which in the case of the Ukrainian understanding is characterized by both the limitlessness of the human soul cognition and the importance of comprehension the common and different in the spiritual organization of other peoples. In particular, the multi-sense mosaic of the ethno-Ukrainian self-awareness of the soul existence as life, love, dream, person, part of the body and embodied desire is argued, the inexhaustibility of the meaning of the soul as a word, term, concept and psychological category is underlined, in addition, it is substantiated the thesis that the exit of feeling and understanding beyond the limits of any scientific cognition is possible in the same way that personally present life creates itself by its existence in the infinity of its own incarnations and meanings. The reaction of the Ukrainian soul to a foreign hiding of faces under the masks of “guise” and “persona” is revealed in an adequate borrowing of the protective method of salvation from insincerity, slyness and deception in the form of the modified Latin concepts of “parsuna” and “portrait”, the dichotomy of borrowed and own is clarified, which accompanies the development of the spiritual identity of Ukrainians in the dualism of the soul-for-oneself and the psyche as a general depersonalized category-for-all that exists in parallel in soul language and psychology, without crossing in its purpose and embodiment. The attention is paid to the fact that over the centuries, an established action on the meaning of the soul remains unanswered, each time acquiring different incarnations: in soulwords as a verbal expression of the soul, expression and appeal to it; in soulsalvation as the return of the soul to itself; in spiritualizing as an active comprehensiveness of mental life in its conscious, subconscious, unconscious and superconscious dimensions. And yet, despite the wide range of forms of spiritual, a soul of a living being remains immeasurable as the soul of life, which will always be the more incomprehensible, the more specific the attempts to grasp it completely and entirely become. The statement that the whole world of a person is embodied in his soul and exists as long as a personal experience continues, as well as the life of the peoples – all those born and related by its psychosocial flow – is reflected. It has been proven that the manifestations of the peoples’ life in its past and present are covered by the concept of the soul and, in a conscious expression, are embodied in interactions on a common field – in the spherical space of communication, which acquires infinite variations of speech existence. Based on this, the need to mark the essence of the soul of everyone who belongs to one of the peoples of the world is inherent in each of these peoples, although it is realized and implemented differently, including going beyond its own borders, which involves capturing as many individuals as possible by imposing your identity on them, embodied in the monopolistic form of cosmopolitanism, chauvinism, fascism, communism, internationalism, globalism or other fluctuations of the ethnic spirit that insatiable by struggle for the primacy. Under the favorable conditions of military expansion for this spirit, it expanded beyond its own phenomenal horizons, always parasitizing on the original ethnic language base – Arabic, Greek, Persian, Latin, French, German, English, Russian and many others. The need in cognition the essence of the Ukrainian soul and its defining properties is revealed, primarily in its desire for deeper self-cognition, the fundamental research basis of which is the joint work of the Ukrainian scientists’ team of the middle of the 20th century “Ukrainian soul” that reflects the main dimensions of the ultra-complex, multi-subject object of study chosen by five scientists: “Ukrainian emotionality” – Ye. Onatskiy, “Ukrainian’s perception of the world” – O. Kulchytskiy, “Family and soul of the peoples” – B. Tsymbalisty, “Soul and song” – M. Shlemkevych, “Bibliographic review” – V. Doroshenko. It is concluded that psychology of the Ukrainian person, the Ukrainian peoples needs a creation of, an adequate for psychosophical cognition-construction, methodology of discovering unknown dimensions of their own development in which the self-movement of psycho-spiritual is possible on the path of self-reflection of its own essence in the boundless vectors of human development that must find and harmonize its own sensory-intellectual soulwords.